The Concepts of Nature and Islamic Economy - Rahmat; M. Yasir Nst; Sugianto; Ade Khadijatul Z. Hrp (International Journal of Economics (IJEC), 2022)
One of the ways humans use natural resources to meet their needs is through production activities. The halal and haram status of the natural resources used in production, as well as the halal and haram status of the production process itself, are some of the guidelines that must be followed. Anyone who uses natural resources and carries out production processes legally will benefit from this principle, which has a significant impact on production operations. On the other hand, whoever uses natural resources illegally and performs production procedures shall be punished with mafsadatan. This research is a qualitative research using literature review method. The data poured is sourced from the collection of literature, with analytical descriptive data analysis techniques. The findings of this study indicate that producers do not sufficiently assume that the production they carry out is halal when carrying out production activities. Natural resources and industrial engineering must also be halal. In Islamic economics, the term "production" refers to efforts to create added value from existing natural resources to ensure human life, so that benefits and blessings will be obtained.